PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF MATERI FPB DI SEKOLAH DASAR - Safitri, Nila; Alim, Jesi Alexander; Noviana, Eddy; Hermita, Neni (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2021)
This study aims to develop a valid and practical interactive instructional media to teach the GCD in elementary schools. This study is the Research and Development, and the reseachers applied the Plomp model consisting of three phases: preliminary research phase, development phase, dan assessment phase. The developed instructional media was validated by 3 experts consisting of media experts and material experts. To test the practicality, the researchers distributed questionnaires to the teacher and students. The data in this study were collected through interviews, observations, and questionnaires. The collected data were then analyzed quantitatively and qualitatively. The developed instructional media was very valid with an average score of 83.96% and was very practical category with an average score of 87.86% from the students and 96.7% from the teachers. Therefore, the interactive instructional media to teach the GCD can be used by elementary students and teachers.